(untitled) (Research, Society and Development, 2021)
Objective: the aim of this work was to explain the implications of the genetic profile (TNF-α polymorphisms in the region-308) in the outcome of different pathologies; and explain how this profile is obtained in the laboratory. Methodology: The salting out technique, according to Miller et al. (1988) was used to explain the reader how the genetic profile of TNF-α is obtained to foresee the outcome of pathologies that are modulated by this cytokine. Results: the product of the amplified digestion of TNF-α genes was obtained, photographed and explained for the reader. Conclusions: the genetic profile may be useful as a predictor for the outcome of different pathologies, so that doctors and dentists may choose the best therapy for each patient.